Price uncertainty and trader-farmer linkage - Fabella, Raul V. (Journal of Public Economics)
We show that the Pareto superiority of loan repayment in kind within a tied credit arrangement to a cash-for-cash scheme under uncertain output price depends crucially on the farmer loan demand elasticity and his risk aversion. For the risk-neutral trader, the cash-for-cash scheme is shown to be Pareto dominated by credit tying and the price premium he offers depends on farmer loan demand elasticity.